Propriedades e parâmetros de escala de filmes de DLC depositados sobre aço ferramenta usando sistema PECVD modificado com cátodo adicional - Ramos, Marco Antonio Ramirez [UNIFESP] (2016)
The research of nanostructured super hard materials in the form of coatings or thin films with advanced properties has enabled the development of new studies providing important scientific and technological developments in different segments of academia and the productive sector. Among these materials, hydrogenated amorphous carbon (aC: H), also known by the acronym DLC (Diamond-like Carbon) has been highlighted because of its excellent properties such as high strength, high hardness, low friction coefficient, biocompatibility, among others. A challenge for researchers of surface engineering is to deposit DLC films with high adhesion to metal substrates for industrial service applications, where the studies of scale become necessary is very important to understand chemically and physically the process of adhesion and the process deposition of the DLC thin films on different types of substrates. The understanding of these parameters enables the study of the phenomena involved in the adhesion and properties of thin films in different positions inside the reactor. In this context it is important to optimize the operational parameters such as the flow of gas constituents, pressure, temperature, percentage between precursor gases, etc. for obtaining homogeneous films with reproductive performance, etc. Thus, this line of research, this doctoral work aims to identify and better understand the issues involved in adhesion between DLC films and different metal substrates, especially with the growing use of techniques, and the techniques conventionally used. For this, the pulsed DC technique PECVD (Plasma Enhanced Chemical Vapor Deposition) with additional cathodes, not explored so far is used for the deposition of interfaces and DLC films in large areas and large internal volumes of especially prepared ballast for this job. Thus, the primary design contribution is the detailed study of this technique order to establish the deposition parameters necessary for the synthesis of high adhesion DLC films and low residual stresses and establish a correlation with the dimensions and shapes of the additional cathode, which is mainly responsible for the high grip. As part of the characterization studies of DLC films, the structural, morphological, mechanical and tribological of synthesized 4 samples will be determined as the dimensions of the additional cathode, which for the first time is being studied for the deposition of DLC. Finally, it emphasizes that this modified PECVD system, patented by the team operates at pressures below 10-3 Torr, featuring a growth process of DLC films via PECVD on a non-collisions, providing high adhesion between the film DLC and the respective substrates. Harder movies, more compliant, less hydrogenated and less friction coefficient were obtained. The uniformity of these DLC films throughout the reactor volume as characteristics of the voltage function applied, in terms of amplitude, width and pulse frequency was studied promises showing results for all segments of industry